Purwokerto Wage Market: A Social Historical Perspective (2000-2024) - Alwania Luthfi Intan Puspita; Carolina Santi Muji Utami (Historia, 2027)
Pasar Wage is a traditional market that has been operating since the colonial era and was renovated in the 1990s. This market has always experienced dynamics, and in the 2000s a fire occurred that caused various social problems. This study seeks to uncover the social aspects and policies implemented from 2000 to 2024, with a focus on the impact of the fire and the revitalization efforts undertaken by the local government. The research method used is a historical method that includes heuristics, source criticism, interpretation, and historiography. It utilizes primary sources in the form of local government archives, reports from the Regional Market Technical Implementation Unit (UPTD) I of the Banyumas Regency Industry and Trade Office, and interviews with traders and market managers. The results show that the fire was a turning point that had a significant impact on the decline in economic activity and the social networks of traders. Although the revitalization succeeded in improving the market infrastructure, these efforts have not been able to fully restore the market's socio-economic function. This study confirms that Pasar Wage is a historical space that reflects the relationship between government policies and the socio-economic dynamics of the local community.